Illustrations and Ambiguity in Eighteen Illustrated Translations of Hans Christian Andersen’s “The Steadfast Tin Soldier” - Alvstad, Cecilia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2008)
AbstractThis articles examines how the interaction between the verbal and the visual relates to the reader-oriented strategy “ambiguity” in eighteen translations of Hans Christian Andersen’s tale “The Steadfast Tin Soldier” as compared to the source text. The translators’ and the illustrators’ different decisions regarding the textual elements that lead to ambiguity are compared to each other in an attempt to uncover the mechanics of ambiguity at work in the different translations. Theoretically, the article is based on Iser’s (1978) textual approach towards the act of reading, and Oittinen’s (2000) work on the visual and the verbal in translation for children.